Folate and B12 serum levels in association with depression in the aged: a systematic review and meta-analysis. (1st September 2016) - Petridou, Eleni Th.; Kousoulis, Antonis A.; Michelakos, Theodoros; Papathoma, Paraskevi; Dessypris, Nick; Papadopoulos, Fotios C.; Stefanadis, Christodoulos
Abstract : Objectives: To systematically review and meta-analyse existing evidence on the association between folate/B12, and depression among the aged people. Methods: Following PRISMA/STROBE guidelines, the Medline abstracts were retrieved using an algorithm comprising relevant MeSH terms. Publications on the association of folate/B12 serum measurements with depression were abstracted independently by two reviewers and included in both gender and gender-specific meta-analyses, following recarculations of published data as appropriate. The Newcastle-Ottawa scale was used to evaluate the quality of included studies. Results: Both gender data were contributed by 11 folate-related (7949 individuals) and 9 B12-related studies (6308 individuals), whereas gender-specific data by 4 folate-related (3409 individuals) and 3 B12-related studies (1934 individuals). A statistically significant overall association between both exposures of interest (low folate and B12 levels) and depression was observed (ORfolate :1.23, 95%CI:1.07–1.43, ORB12 :1.20, 95%CI:1.02–1.42). Gender-specific estimates pointed to a statistically significant positive association between low B12 levels and depression only among women (OR:1.33, 95%CI:1.02–1.74); the gender specific associations of low folate levels with depression were, however, non-significant and of counter-direction (ORfemales :1.37, 95%CI:0.90–2.07; ORmales :0.84, 95%CI:0.57–1.25). Conclusion: Low folate and B12 serum levels seem to be associated with depression in the aged. The gender-specific analyses are confined to a positive association of low B12 with depression among older women and call for further research in this direction.